Pengelolaan Sampah dalam Upaya Pengendalian Pencemaran Lingkungan oleh Desa Adat Padangtegal, Kecamatan Ubud, Kabupaten Gianyar - I Kadek Purwadi Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2022)
Indonesia is a country that is ranked 4 (four) in the world, so it cannot be denied that the problem of waste is a complex problem faced by the Government, waste is one of the biggest problems that are often encountered by people in other parts of the world, waste itself is a leftover from activities and activities. human consumption, which has been wasted and has no economic value anymore. Garbage is a problem faced in almost all parts of the world. Seeing the many waste problems that occurred, the Padangtegal Traditional Village built a Compost House as a form of the Village's concern for the waste problem. This study aims to examine environmental pollution by the traditional village of Padangtegal, Ubud District. The method used is empirical legal research. This research uses a statutory approach and is carried out by examining and studying laws or other regulations such as awig-awig and pararem in accordance with the issues in question, in which the norms are hierarchically arranged in the arrangement of legal norms. Sources of data in this study are primary data and secondary data. The results of the study indicate that the implementation of waste management in the Padangtegal Traditional Village has been running well according to applicable regulations and in its implementation the Padangtegal Traditional Village manages waste management independently through management.